PERANCANGAN SISTEM INFORMASI PENJADWALAN MATA KULIAH DENGAN METODE SDLC (CYSTEM DEVELOPMENT LIFE CYCLE) - Wahyu Rizki; Rayuwati Rayuwati; Husna Gemasih (Universitas Gajah Putih, 2022)
From the student aspect, it is necessary to pay attention to the presence or absence of other lectures in the courses taken by students, apart from being seen from the student aspect, it is also necessary to look at the lecturer's aspect, namely the possibility that the lecturer concerned also cannot teach properly because he is on duty or are studying at a further level or because they already have a teaching schedule in other majors, in order to produce good components in the context of preparing the schedule, the academic side must make some correlations between the components concerned so that there are no cases of schedule collisions or clashes. Based on the problems above, at least there are several methods that can be used to simplify the scheduling process, including the SDLC method. SDLC is indeed not the best method of solving various problems, but for cases like SDLC scheduling it is one of the best because this method quickly finds the minimum solution while still analyzing. In general, lecture scheduling using the SDLC method ideally will consider several things, namely the time of implementation, such as being carried out from Monday to Friday or Saturday, from 07.00 to 18.00, teaching staff such as the availability of suitable and willing teaching staff to be scheduled at any time and anywhere, the study room must also be adjusted to the number of students, the more students the need for room availability will also increase.